Dystocia due to ventral abdominal hernia with hysterocoele in a crossbred cow and its management: Dystocia due to ventral abdominal hernia with hysterocoele in a crossbred cow and its management - Rangasamy, T; Suresh Kumar, R; Pugazharasi, C; Kalyan, U S; Sarath, T; Krishnakumar, K (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A full term pregnant pluriparous Jersey crossbred cow was presented with the history of difficulty in parturition, bloody vaginal discharge and straining with distended left ventral abdominal wall and the cow was recumbent. Based on the clinical examination, the case was diagnosed as dystocia due to ventral abdominal hernia with hysterocoele and its successful per-vaginal delivery was reported in this communication.